Responses of sap flow density of two shrub species to rainfall classes on the semiarid Loess Plateau of China - Fang, Weiwei; Lu, Nan; Liu, Jianbo; Li, Ruiping; Wang, Yuxiao (Frontiers in Plant Science, 2023)
Rainfall events can determine a cascade of plant physiological and ecological processes, and there is considerable interest in the way that rainfall modifies plant water flux dynamics. The sap flow density (SF) of the planted species of Vitex negundo and Hippophae rhamnoides, on the Loess Plateau of China was monitored using the heat balance method from 2015 to 2017. The results showed that SF responded differently to rainfall classes because of the changing meteorological and soil water content (SWC) conditions. For class 1: 0.2–2 mm, SF increased by 14.36–42.93% for the two species, which were mainly attributable to the effect of solar radiation and vapor pressure deficit after rainfall. For class 2: 2–10 mm, SF remained nearly stable for V. negundo and decreased for H. rhamnoides because of the relative humidity’s effect. For class 3: > 10 mm, SF increased significantly because of increased SWC and the increasing response to solar radiation. The increased percentage of SF was relatively higher for V. negundo when rainfall was less than 20 mm, while the value was higher for H. rhamnoides when rainfall was greater than 10 mm. Further, V. negundo’s water potential increased at the soil-root interface (ψ0) and ψL, indicating that the plant, which has shallower roots and a coarser of leaf and bark texture, considered as anisohydric species and used precipitation-derived upper soil water to survive. The relatively consistent ψL and ψ0 for H. rhamnoides, which has deep roots and leathery leaves, indicated that this species was considered as isohydric species and insensitive to the slight change in the soil water status. The differed response patter and water use strategies between the two species showed that species as V. negundo are more susceptible to frequent, but small rainfall events, while larger, but less frequent rainfall events benefit such species as H. rhamnoides. This study quantified the effect of environmental factors for SF variation. The results could help formulate a selection process to determine which species are more suitable for sustainable management in the afforestation activities under the context of more frequent and intense rainfall events.